A historical and geographical analyses of peculiarities of establishing Yaremche-Vorokhta resort area, the largest in the Eastern Carpathians of the Austro-Hungarian period - Rutynskyi, Mykhailo Josypovycz (Journal of Education, Health and Sport, 2015)
Rutynskyi Mykhailo. A historical and geographical analyses of peculiarities of establishing Yaremche-Vorokhta resort area, the largest in the Eastern Carpathians of the Austro-Hungarian period. Journal of Education, Health and Sport. 2015;5(7):475-488. ISSN 2391-8306. DOI 10.5281/zenodo.21156 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A475-488 https://pbn.nauka.gov.pl/works/593179 http://dx.doi.org/10.5281/zenodo.21156 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 15.07.2015. A HISTORICAL AND GEOGRAPHICAL ANALYSES OF PECULIARITIES OF ESTABLISHING YAREMCHE-VOROKHTA RESORT AREA, THE LARGEST IN THE EASTERN CARPATHIANS OF THE AUSTRO-HUNGARIAN PERIOD Mykhailo Rutynskyi* *Ivan Franko National University of Lviv, 41, Doroshenko St., UA – 79000 L’viv, Ukraine, gm_lviv@i.ua Abstract This paper analyses the historical and geographical conditions and the peculiarities of formation of the spa and climatic health resort area along the Prut river in the Eastern Carpathians at the end of XIX-th and the beginning of the XX-th century. The main centers of that climatic health resort area were mountainous villages Yaremche, Dora, Tatariv, Mykulychyn, Vorokhta located along the Trans-Carpathian railway line opened at the end of the nineteenth century. The peculiarities of establishing the health-recreation specialization of the settlements within the studied mountainous area were analyzed. The process of consolidation of the Hutsul villages in the polycentric Yaremche-Vorokhta resort area of the Alpine spa and climatic health resorts type is found out. Key words: spa and climatic health resort, historical and geographical analyses, health and recreational specialization, natural health-improvement resources, resort recreation, stages of resort area development.